Association between gene polymorphisms and obesity and physical fitness in Korean children - Kim, Hyun Jun; Lee, Sang Yeoup; Kim, Cheol Min (Biology of Sport, 2018)
Obesity is affected by genetic factors and environmental influences. This research was undertaken to identify single nucleotide polymorphisms (SNPs) related to obesity and physical fitness and then to analyse and compare interactions between physical fitness and obesity-associated genotypes. To investigate relationships between physical fitness and major SNPs previously reported to be related to obesity, 68 SNPs in 32 genes were genotyped in 71 Korean children. Tests were conducted to evaluate five elements of physical fitness (speed, aerobic endurance, muscular endurance, muscular strength, and flexibility). The results obtained showed significant (P<0.02) differences in physical fitness scores for the following genotypes: CNR1 (rs1049353; GG), LEP (rs7799039; AA+AG), HHEX (rs1111875; TT), GC (rs16847015; TG+GG), LRP5 (rs4988300; GG+GT), NPY2R (rs2880415; CT+CC), PPY (rs231472; GG), UCP2 (rs660339; CT+TT), CDKN2B (rs10811661; AA+AG), and ADIPOQ (rs266729; CG+GG). Ten physical fitness-related genotypes were newly identified during the present study. This study suggests that classification of genotypes by physical fitness level could be used as an index for predicting the risk of obesity and for selecting individuals for intervention programmes. Furthermore, the study shows that even children participating in the same physical fitness improvement programme can exhibit different genotype dependencies.